BEYOND CONTROL ADOLESCENTS COPING TOWARDS DYSFUNCTIONING FAMILY: INTEGRATING ROLES WITH FAMILY SYSTEM THEORY - Sarnon, Norulhuda (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to explore on how the beyond control adolescents coping with family issues through the roles they play. This study uses qualitative methods with grounded theory approach and analytical tools;open, axial and selective coding when analysing data. 5 interview questions were developed to look at the adaptation of thebeyond control adolescent’s roletowards issues in the family. A total of 36 juvenile undergoing court orders and under the probation official’ssupervision were involved in thisstudy. The study found five types of roles played by the adolescents towards family issues, namely (i) protecting, (ii) reconciling, (iii) self-separation, (v) rebelling and (vi) sacrifice. Studies have also found that informants try to protect their family members in the event of domestic violence, reconcile conflicting or divorced parents, self-separate when they are often being scolded, rebels when being ignored and sacrifice when parents do not have sufficient sources of income or are chronically ill. This study shows that the beyond control adolescents experiences in adjusting themselves with the family affect their today’s behaviour. An adaptive coping role is a valuable resource that could help the professionals in the field to formulate behavioural change strategy according to the family issues that they are facing.